Treating justice involved persons with mental illness: preliminary evaluation of a comprehensive treatment program - Morgan, Robert D. (Criminal justice and behavior, 2014)
In this article, we present the results of a preliminary evaluation of a comprehensive treatment program specifically designed to treat co-occurring issues of mental illness and criminal risk in persons with mental illness (PMI) that are criminal justice involved. Participants include 47 incarcerated male PMI in a secure psychiatric prison or a residential treatment facility. Of the 47 participants, 31 (66%) completed the program, attended 94% of all sessions, completed 83% of assigned homework, and actively participated in treatment sessions as evidenced by participation ratings. Change was examined using a four-tiered assessment strategy, including pre?post significance testing, magnitude of effect sizes, clinical cutoffs, and reliable change indices. Results showed evidence of strong therapeutic alliance and treatment program satisfaction, as well as symptom reduction and some evidence for reduced criminal thinking. Program modifications and implications for enhancing service delivery to justice involved PMI are discussed.